OBJEKTIVITAS SEMIOTIKA (ILMU TANDA) MENYINGKAP FIRMAN (TANDA-TANDA KEBESARAN) TUHAN - MARWAN, IWAN MARWAN (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2017)
AbstractThe fact of life is a collection of puzzles, questions or enigmas, which demanded a search of answers, which is called truth (truth). Truth belongs to God and man just looking for clues, evidence, and signs of truth in logic. The review was directed at the thought of how objectivity as the science of semiotics sign looked and positioning and unveil the word (the signs of the greatness of) God.View of semiotics towards God's signs include signs qauliyah and signs qauniyah. Mark qauliyah is speech, sounds, fonts or text, while the sign of kauniyah is a natural phenomenon, social events, unusual in nature. The second verse is a sign containing a variety of usage marks, codes and meanings in it, though it did not close the possibility to look at the relationships the metaphysical, theological, philosophical and scientific in it. Reading this semiotic, can be considered as a reading open, plural and comprehensive, which can spread out almost all of the realities of life.